Conocimientos y prácticas preventivas de its Y vih-sida, en estudiantes del Colegio”Manuel Cabrera Lozano extensión Motupe” sección matutina, periodo septiembre 2009 - abril 2010 - Cuenca Samaniego, Enma Lucia (2010)
He/she was carried out a study of descriptive type and of court trasversal in students of the school “MANUEL GOATHERD LOZANO” EXTENSION MOTUPE MORNING SECTION with the objective of identifying their conocimentos and you practice preventive of ITS-VIH/SIDA, likewise to know the participation of the educational institution in the promotion of the sexual health of the students. Later on you organizes an intervention proposal that I guide the adolescents to the autocuidado of their sexual health. The sample was conformed by 298 students to those that you applies a survey, as technique for recabar information whose objective was to identify the knowledge and you practice preventive ITS-VIH/SIDA, likewise the applied interview to the Coordinator of the Institution and Educational of Vocational Orientation whose purpose was to know the participation of the educational unit in the orientation of the sexual health of the students. The two used techniques are instruments that allow to complete the objectives proposed in the investigation. The results of the study indicate that 59,04% of the masculine sex and 67% of feminine sex know on the ITS AND VIH/SIDA, likewise of the realized interview to the Coordinator and Educational of Vocational Orientation you concludes that the Institution in study includes topics of sexual education in the subject of Vocational Orientation, which a weekly hour is dictated the students with the purpose of offering them education has more than enough knowledge and you practice of prevention of ITS AND VIH/SIDA.